The suitability of ASEAN for a regional currency arrangement - Bayoumi, Tamin (2001)
Analyzes the potential benefits and cost associated with a currency union for ASEAN and discusses the preconditions for success. Concludes with a discussion on the implications of a currency union for ASEAN countries.